(untitled) (LACCEI, 2024)
The objective of this study was to implement the preventive maintenance program to increase the availability of the production machines of the company NOVAGRO-AG S.A.C.-Trujillo -2022. The research had a quantitative approach, was applied, with an explanatory level and Preexperimental design. Techniques such as observation and documentary analysis were used. In addition, a convenience sampling was applied to the critical machinery. As a result of the study, the powder mixer was identified as the machinery with the highest level of criticality and a Failure Mode and Effect Analysis (FMEA) was applied on it. Finally, the implementation of a preventive maintenance program allowed to increase the availability of the Powder Mixer in the production area of NOVAGRO-AG S.A.C. - Trujillo - 2022, which went from an initial availability of 87.35% to a final availability of 95.02%.